Synthesis of Fe3O4/Hydroxyapatite Nanocomposites: Structural, Surface, and Magnetic Characterization - Fadli, Ahmad; Prabowo, Agung; Drastinawati, Drastinawati; Wandika Putra, Bima; Sugesti, Heni; Puspasari, Febriyati (Indonesian Journal of Chemistry, 2026)
Magnetite/hydroxyapatite (Fe3O4/HA) nanocomposites are promising materials for biomedical applications, particularly in targeted drug delivery. This study investigates the effects of hydrothermal reaction time and FeCl3 precursor concentration on the structural, morphological, and magnetic properties of Fe3O4/HA composite powders synthesized via a one-pot hydrothermal method. The resulting composites exhibit biphasic structures comprising magnetite (cubic phase) and hydroxyapatite (hexagonal phase) crystallites, with average sizes ranging from 22 to 30 nm. Both increased reaction time and FeCl3 concentration contributed to the growth of crystal size. A notable enhancement in specific surface area was observed, increasing from 48.21 to 67.41 m2/g as FeCl3 concentration decreased from 0.15 to 0.05 M at a fixed reaction time of 15 h. Magnetic characterization revealed that the composites exhibited superparamagnetic behavior, with the highest saturation magnetization (Ms) reaching 17.27 emu/g. These results demonstrate that tuning synthesis parameters can optimize the structural and magnetic properties of Fe3O4/HA nanocomposites, making them strong candidates for use in controlled drug delivery systems.